Great Yorkshire Livestock Show Attendees’ Attitudes about Agriculture - Brytann Busick; Holli Leggette; Gary E. Briers; Holly Whitaker; Jean A Parrella (Journal of Applied Communications, 2023)
The purpose of our research was to determine if attending a U.K. livestock show changed attendees’ attitudes about agriculture and to compare those changes in attitudes to attendees of a U.S. state fair similar in size and dynamic. The sample was livestock show attendees at the Great Yorkshire Show (GYS). The mixed-method design included a then and now semantic differential scale with bipolar adjective pairs to measure attendees’ attitudes about agriculture before and after the experience and qualitative interviews with photo elicitation to learn about how attendees developed attitudes about agriculture. Participants had positive attitudes about agriculture before they attended the Show and had more positive attitudes after attending. Participants had more positive attitudes before and after attending the Show than did California State Fair attendees. In addition, participants lacked prior experiences with agriculture, but attending the GYS provided them the opportunity to develop positive attitudes through cognitive, behavioral, and environmental factors. Fair attendance should be promoted because they provide unique opportunities for experiential learning and U.S. fairs should adopt experiential tactics used at the GYS. Further research is needed to better understand how GYS attendees developed positive attitudes about agriculture prior to attending the Show and what elements of the GYS experience were most influential to attendees’ attitude development.
Keywords: attitudes; agriculture; California State Fair; Great Yorkshire Livestock Show; mixed methods